SISTEM ALAT MONITORING UNTUK PENGENDALI SUHU DAN KELEMBABAN GREENHOUSE BERBASIS INTERNET OF THINGS - Arafat Arafat; Ibrahim Ibrahim (Universitas Lambung Mangkurat, 2020)
Greenhouse is an agricultural technology to protect plants from uncertain weather, with the Greenhouse will be able to maintain and distribute temperature, soil moisture, sunlight, and air humidity evenly with an optimal level. Even so the environmental conditions inside the Greenhouse will always change due to the influence of the weather environment outside the Greenhouse which is uncertain, so there is a need for monitoring so that plants inside the Greenhouse can grow optimally. With IoT (Internet of Things) technology, Greenhouse farmers do not need to visit the Greenhouse to monitor and control the environment inside the Greenhouse. This is because with the IoT technology Greenhouse farmers can monitor and control v1ia an Android smart phone. The things that can be monitored are temperature, humidity of the room, soil moisture, sunlight, water discharge, and soil moisture, besides that farmers can also control the temperature and humidity of the Greenhouse environment, as well as the provision of water to plants in the Greenhouse. The system used in this study uses ESP32 as a control center and uses DHT11, Soil Moisture, as a sensor to measure IoT temperaturei, humidityi and soil moisture in the greenhousei. As a control in the greenhouse there are two control outputs, namely water pump 1 and water pump 2. ESP32 will read the temperature, humidity and soil moisture sent from the DHT11 sensor which will determine whether the water pump will turn on or not. To read the soil moisturei sensor used is capacitivei soil moisturei, if the soil moisture reaches a predetermined threshold, the water pump 2 will turn on and drain the water into a poly bag through drip drops.